2023
DOI: 10.1002/tox.23879
|View full text |Cite
|
Sign up to set email alerts
|

CircWHSC1 serves as a prognostic biomarker and promotes malignant progression of non‐small‐cell lung cancer via miR‐590‐5p/SOX5 axis

Abstract: Dysregulated circWHSC1 has been shown to play potential roles in diverse cancer types, including ovarian cancer, endometrial cancer and hepatocellular carcinoma (HCC). The objective of this study was to investigate its expression, underlying role and regulatory mechanism in non‐small‐cell lung cancer (NSCLC). The expression of circWHSC1 was determined by real‐time PCR. After knockdown of circWHSC1 expression in NSCLC cells, the proliferation, migration, and invasion were detected using CCK‐8, colony formation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Lung cancer is the most prevalent cancer type that involves different mechanisms 45,46 . A previous report has shown that PRMT6 is largely expressed in lung cancer tissues, and its abrogation significantly suppressed the growth of lung cancer cells 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is the most prevalent cancer type that involves different mechanisms 45,46 . A previous report has shown that PRMT6 is largely expressed in lung cancer tissues, and its abrogation significantly suppressed the growth of lung cancer cells 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) is the most common histological type of lung cancer ( 81 ). Many studies have suggested that SOX5, as an oncogene, is involved in the occurrence and development of NSCLC ( 61 ). Li et al.…”
Section: Sox5 In Multiple Human Cancersmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) is the most common histological type of lung cancer (81). Many studies have suggested that SOX5, as an oncogene, is involved in the occurrence and development of NSCLC (61). Li et al found that SOX5 was highly expressed in tissues and cell lines of NSCLC, and highly expressed SOX5 could promote the development of NSCLC (62), and suggested that the mechanism might be to drive the malignant potential of NSCLC through interaction with YAP1 (82).…”
Section: Lung Cancermentioning
confidence: 99%